A systematic review of functional near-infrared spectroscopy-based task paradigms in stroke rehabilitation - Huang, Yuping; Zhan, Xiaoxuan; Zeng, Huizi; Li, Shuyin; Shi, Jingqin; Cui, Zhenhua; Fan, Qianqian; Li, Binbin; Sui, Yanfang; Liang, Fengyan; Song, Zhenhua (Frontiers in Human Neuroscience, 2026)
Precision in assessing neurological function after stroke is key to optimizing the efficacy of rehabilitation. Functional near-infrared spectroscopy (fNIRS) provides a highly ecologically valid assessment of cortical activation and functional reorganization after stroke by monitoring cortical hemodynamic changes during different tasks. However, the current fNIRS task paradigm lacks systematic integration for standardized design and clinical translation strategies, and fragmented evidence is difficult to converge into actionable practice guidelines. To fill this gap, this paper systematically reviews the application of fNIRS in motor, cognitive, language, and dual-task paradigms in stroke rehabilitation research. It reveals the clinical value of different paradigms for neurological function assessment and proposes adaptive task designs that fit the functional characteristics of patients with stroke. This study emphasizes the importance of personalized and ecological paradigms, providing a theoretical basis and practical reference for subsequent standardized research on fNIRS task paradigms and developing clinical application standards.